The Frequency and Outcome of Acute Kidney Injury in a Tertiary Hospital: Which Factors Affect Mortality?. Issue 7 (10th April 2015) - Ulusoy, Sukru; Arı, Derya; Ozkan, Gulsum; Cansız, Muammer; Kaynar, Kubra
Abstract Acute kidney injury (AKI) is a major cause of mortality and morbidity in hospitalized patients. Incidence and mortality rates vary from country to country, and according to different in‐hospital monitoring units and definitions of AKI. The aim of this study was to determine factors affecting frequency of AKI and mortality in our hospital. We retrospectively evaluated data for 1550 patients diagnosed with AKI and 788 patients meeting the Kidney Disease: Improving Global Outcomes (KDIGO) guideline AKI criteria out of a total of 174 852 patients hospitalized in our institution between January 1, 2007 and December 31, 2012. Staging was performed based on KDIGO Clinical Practice for Acute Kidney Injury and RIFLE (Risk, Injury, Failure, Loss of kidney function and End‐stage renal failure). Demographic and biochemical data were recorded and correlations with mortality were assessed. The frequency of AKI in our hospital was 0.9%, with an in‐hospital mortality rate of 34.6%. At multivariate analysis, diastolic blood pressure (OR 0.89, 95% CI 0.87–0.92; P < 0.001), monitoring in the intensive care unit (OR 0.18, 95% CI 0.09–0.38; P < 0.001), urine output (OR 4.00, 95% CI 2.03–7.89; P < 0.001), duration of oliguria (OR 1.51, 95% CI 1.34–1.69; P < 0.001), length of hospitalization (OR 0.83, 95% CI 0.79–0.88; P < 0.001), dialysis requirement (OR 2.30, 95% CI 1.12–4.71; P < 0.05), APACHE II score (OR 1.16, 95% CI 1.09–1.24; P < 0.001), and albumin level (OR 0.32, 95% CI 0.21–0.50; P < 0.001) were identified as independent determinants affecting mortality. Frequency of AKI and associated mortality rates in our regional reference hospital were compatible with those in the literature. This study shows that KDIGO criteria are more sensitive in determining AKI. Mortality was not correlated with staging based on RIFLE or KDIGO. Nonetheless, our identification of urine output as one of the independent determinants of mortality suggests that this parameter should be used in assessing the correlation between staging and mortality.